2014
DOI: 10.1097/aln.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Brain Neuroplastic Changes Accompany Anxiety and Memory Deficits in a Model of Complex Regional Pain Syndrome

Abstract: Background Complex regional pain syndrome (CRPS) is a painful condition with ~50,000 annual new cases in the United States. It is a major cause of work-related disability, chronic pain after limb fractures and persistent pain after extremity surgery. Additionally, CRPS patients often experience cognitive changes, anxiety and depression. The supraspinal mechanisms linked to these CRPS-related comorbidities remain poorly understood. Methods We used a previously-characterized mouse model of tibia fracture/cast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 100 publications
5
78
0
Order By: Relevance
“…In the present study, we observed that in the EPM test CFAinflammatory mice had a decreased open-arm and close-arm entry alternation and spent more time licking and favoring the affected paw. It has been reported that mice with chronic pain spend less time exploring novel objects in the novel-object recognition test [39,40]. Thus, attention toward the source or location of the pain may interrupt or ignore the aggressive behavior from aggressors in the SD stress process.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we observed that in the EPM test CFAinflammatory mice had a decreased open-arm and close-arm entry alternation and spent more time licking and favoring the affected paw. It has been reported that mice with chronic pain spend less time exploring novel objects in the novel-object recognition test [39,40]. Thus, attention toward the source or location of the pain may interrupt or ignore the aggressive behavior from aggressors in the SD stress process.…”
Section: Discussionmentioning
confidence: 98%
“…BDNF is a key signaling molecule involved in a wide range of central functions and neuronal plasticity, including modulatory actions in the hippocampus of relevance to learning, memory, neurogenesis, and mood control (89)(90)(91)(92)(93). Memory impairment after surgery has also been associated with reduced BDNF expression (94)(95)(96)(97). Conditional knockout of BDNF in the forebrain impairs hippocampal-dependent learning in mice (98,99).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind the chronification of pain are not clear with hypotheses ranging from dysregulated descending inhibitory pathways 35 to primary nociceptor plasticity 18 and altered central pain processing. 55 After injury, the ECM-neuron cross talk is particularly relevant because pain is associated with spinal plasticity, 20 including changes in dendritic architecture (dendritic length and branching and dendritic spine density and morphology) 46 that often rely on structural proteins. 48 These plastic changes could be maladaptive, resulting in central sensitization of second-order spinal neurons and, ultimately, the chronification of pain.…”
Section: Extracellular Matrix and The Chronification Of Painmentioning
confidence: 99%